A checklist of Indonesian scale insects (Hemiptera: Coccomorpha) - Zarkani, Agustin; Apriyanto, Dwinardi; Turanli, Ferit; Ercan, Cansu; Kaydan, Mehmet Bora (Zootaxa, 2021)
Scale insects (Hemiptera: Sternorryncha: Coccomorpha) are a very important insect group containing numerous pests of woody and herbaceous plants worldwide. The only complete study of any scale insects in Indonesia was by D.J. Williams on the mealybugs (Pseudococcidae sensu lato), published in 2004; the other scale insect families have only been documented in various small publications. Here we provide a complete checklist of the scale insects of Indonesia, which now contains 364 species belonging to 136 genera in 16 families. The family Diaspididae is the most diverse, with 158 species belonging to 44 genera, followed by Pseudococcidae with 105 species belonging to 32 genera, and Coccidae with 65 species belonging to 22 genera. The other families are, in order of size: Monophlebidae (26 species belonging to 9 genera), Rhizoecidae (12 species belonging to 4 genera), Asterolecaniidae (11 species belonging to 5 genera), Leconodiaspidae (7 species belonging to 3 genera), Cerococcidae (5 species belonging to 3 genera), Xenococcidae (5 species belonging to 2 genera), Ortheziidae (4 species belonging to 3 genera), Eriococcidae (4 species belonging to 2 genera), Aclerdidae (2 species belonging to 1 genus), and Kermesidae (1 species belonging to 1 genus).